2015
DOI: 10.1155/2015/795138
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Effect of Plasmon Energy Transfer and Recombination Barrier in a Novel TiO2/MgO/Ag Working Electrode for Dye-Sensitized Solar Cells

Abstract: Novel TiO2/MgO/Ag composite electrodes were applied as working electrodes of dye-sensitized solar cells (DSSCs). The TiO2/MgO/Ag composite films were prepared by dip coating method for MgO thin films and photoreduction method for Ag nanoparticles. The MgO film thicknesses and the Ag nanoparticle sizes were in ranges of 0.08–0.46 nm and 4.4–38.6 nm, respectively. The TiO2/MgO/Ag composite films were characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The TiO2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although the introduction of one-dimensional TiO 2 nanostructure can greatly improve the electron transfer rate, the TiO 2 nanomaterial has its own weakness, that is, poor light-harvesting ability and dye adsorption [22]. Studies have shown that some metal nanoparticles can improve the energy level structure of the TiO 2 nanomaterials and enhance the ability of light absorption [23]. Wang et al found that TiO 2 powder mixed with Er 3+ showed a higher photocatalytic activity, compared with the pure TiO 2 powder [24].…”
Section: Introductionmentioning
confidence: 99%
“…Although the introduction of one-dimensional TiO 2 nanostructure can greatly improve the electron transfer rate, the TiO 2 nanomaterial has its own weakness, that is, poor light-harvesting ability and dye adsorption [22]. Studies have shown that some metal nanoparticles can improve the energy level structure of the TiO 2 nanomaterials and enhance the ability of light absorption [23]. Wang et al found that TiO 2 powder mixed with Er 3+ showed a higher photocatalytic activity, compared with the pure TiO 2 powder [24].…”
Section: Introductionmentioning
confidence: 99%
“…The TiO 2 electrodes were screen printed from a TiO 2 paste (Dyesol) 3 times on a fluorine-doped-tin-oxide (FTO) glass substrate (2x3 cm 2 in size) and sintered at 450°C for 30 min. A 200-mesh was used to obtain TiO 2 layers having area of 0.5 x 1.2 cm 2 and a thickness of approximately 14 µm [6]. Then, the TiO 2 films were dipped in a magnesium acetate solution with a concentration of 1x10 -3 M at 40°C for 30 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid leakage and volatilization of liquid electrolytes, composite poly(ethylene oxide) PEO/TiO 2 /KI/I 2 electrolyte in acetronitrile with ethanol additive demonstrated an increase in ionic conductivity of the solid polymer electrolyte [5]. In order to decrease electron-hole recombination and increase light absorption at working electrodes, a 0.1 m thick MgO layer was dip coated and 4.4 nm Ag nanoparticles were photoreduced onto the conventional porous TiO 2 layer, respectively [6]. Without expensive apparatus, optimization of materials for the photoanode, the electrolyte and the CEs of the DSSCs should enable reasonable energy-conversion performances.…”
Section: Introductionmentioning
confidence: 99%